Sequence and transcriptional pattern of the essential Escherichia coli secE-nusG operon. - Downing, W L (1990)
Two genes, secE and nusG, situated between the tufB and ribosomal protein rplKAJL operons in the rif region at 90 min on the Escherichia coli chromosome, have been sequenced and characterized. The secE gene encodes a 127-amino-acid-long polypeptide, which is an integral membrane protein essential for protein export (P. J. Schatz, P. D. Riggs, A. Jacq, M. J. Fath, and J. Beckwith, Genes Dev. 3:1035-1044, 1989). The nusG gene encodes a 181-amino-acid-long polypeptide and is involved in transcription antitermination. The protein product of nusG is essential for bacterial viability. The secE-nusG genes are cotranscribed, with transcripts initiated at the PEG promoter and terminated at the Rho-independent terminator in the region of the rplK promoter. The majority of transcripts are processed at a number of sites in the 5' untranslated leader region by RNase III and are possibly also processed by a second unidentified nuclease. The role of transcript processing in the regulation of secE and nusG has not yet been established. The juxtaposition and coregulation of a protein export factor and a transcriptional factor raise questions concerning a functional connection between the two processes.